Caryophyllidean tapeworms (Platyhelminthes: Eucestoda) from freshwater fishes in Japan - Scholz, T; Shimazu, T; Olson, P D; Nagasawa, K (Folia parasitologica, 2001)
The following caryophyllidean tapeworms were found in freshwater fishes from Japan (species reported from Japan for the first time marked with an asterisk): family Caryophyllaeidae: Paracaryophyllaeus gotoi (Motomura, 1927) from Misgurnus anguillicaudatus (Cantor); Archigetes sieboldi Leuckart, 1878 from Pseudorasbora parva (Temminck et Schlegel) and Sarcocheilichthys variegatus microoculus Mori (new hosts); family Lytocestidae: *Caryophyllaeides ergensi Scholz, 1990 from Tribolodon hakuensis (Günther), T. ezoe Okada et Ikeda, Hemibarbus barbus (Temminck et Schlegel) and Chaenogobius sp. (new hosts); Khawia japonensis (Yamaguti, 1934) from Cyprinus carpio Linnaeus; K. sinensis Hsü, 1935 from H. barbus (new host) and C. carpio; *K. parva (Zmeev, 1936) from Carassius auratus langsdorfii Valenciennes in Cuvier et Valenciennes and Carassius sp. (new hosts); and *Atractolytocestus sagittatus (Kulakovskaya et Akhmerov, 1962) from C. carpio; family Capingentidae: *Breviscolex orientalis Kulakovskaya, 1962 from H. barbus (new host); and Caryophyllidea gen. sp. (probably Breviscolex orientalis) from C. carpio. The validity of C. ergensi, originally described from Leuciscus leuciscus baicalensis from Mongolia, is confirmed on the basis of an evaluation of extensive material from Japan. Atractolytocestus sagittatus (syn. Markevitschia sagittata) is tentatively considered a valid species, differing from the only congener, A. huronensis Anthony, 1958, in its considerably greater number of testes.
Keywords: sladká voda; máloostní; Female; Cypriniformes; Animals; Japonsko; ženské pohlaví; mužské pohlaví; Male; Fresh Water; zvířata; Japan; Cestoda